Mediteranski miti od antike do 18. stoletja = Mediterranean Myths from Classical Antiquity to the Eighteenth Century - Kokole, Metoda; Šašel Kos, Marjeta; Murovec, Barbara; Talbot, Michael (ZRC SAZU, Založba ZRC, 2006)
Proceedings of the interdisciplinary seminary held at the Italian Cultural Institute in Ljubljana in 2004. It includes the articles of the following contributors: Maria Cecilia d'Ercole, Dinko Fabris, Stanko Kokole, Gabrielle Kremer, Irena Lazar, Marko Marinčič, Andreja Maver, Barbara Murovec, Giovanna Perini, Renato Raffaelli, Hendrik Schulze, Michael Talbot.